T-weakly Hopfian modules - Abderrahim El Moussaouy, M'Hammed Ziane, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The concept of Hopfian modules has been extensively studied in the literature. In this paper we introduce the notion of T-weakly Hopfian modules which is a proper generalization of Hopfian modules. We present some properties of these modules. Further, the T-weakly Hopficity of modules over truncated polynomial rings are considered.